Barriers to accessing TB clinics among Myanmar TB patients attending a Thailand-Myanmar border hospital: a qualitative approach - Theint Theint Lwin; Tawatchai Apidechkul; Jongkon Saising; Panupong Upala; Ratipark Tamornpark (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This qualitative approach study aimed to understand the barriers to accessing a tuberculosis (TB) clinic in a Thai hospital as experienced by TB patients from Myanmar living on the Thailand-Myanmar border. Design/methodology/approach - Twenty-two participants were asked to provide information. In-depth interviews were used to gather the information. Each interview lasted 40 min. Findings - TB patients from Myanmar experience several barriers to accessing TB treatment and care at Mae Sai Hospital, such as language and economic problems, although they are very satisfied with the quality of service and positive attitude of the health care providers. A long waiting time and lack of explanation of the pathogenesis of TB were noted as negative aspects by the patients and their relatives. The medical staff at the TB clinic were negatively affected by the excessive workload and unsuitability of some methods or technologies. Using budgetary subsidies from agencies to fund TB care and treatment was not sustainable. Foreign TB patients are not subsidized by the national universal insurance scheme of Thailand, and sending TB patients back to their home country is sometimes unavoidable. Originality/value - Thailand and Myanmar should strengthen their collaboration and develop a system to improve the quality of TB patient care and management for those who are living in poverty and lack education, by focusing on reducing language and economic barriers to accessing health care services including support for medicines and laboratory materials related to TB case management among these populations.